Multiple anastomotic complications following repair of oesophageal atresia with tracheoesophageal fistula: A report of two cases - Prashant Jain; Pinaki R Debnath; Vishesh Jain; Rajiv Chadha; Subhasis R Choudhury; Archana Puri (Wolters Kluwer Medknow Publications, 2011)
This report describes the clinical course and management of two children with multiple anastomotic complications following primary repair of oesophageal atresia (EA) with distal tracheoesophageal fistula (TEF). These included anastomotic leak and stricture, oesophageal perforation during antegrade dilatation, and finally a recurrent fistula between the oesophagus and the tracheo-bronchial tree. Ultimately, after multiple operative interventions, a successful outcome was achieved in both patients with preservation of the native oesophagus. The anastomotic complications following primary repair of EA with TEF are discussed, with special reference to difficulties in the management of recurrent TEF.